New fruit crops for desert regions - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
By searching deserts around the world, Israeli scientists have found six fruit and nut trees that show promise as orchard crops for arid regions. The project began in 1984 and initially yielded 27 potential trees, but these have been narrowed down...